Overview of the situation of sheep production in the area of Eordea Kozani - GIANNENAS (Η. ΓΙΑΝΝΕΝΑΣ) I.; LEONIDIS (Γ. ΛΕΩΝΙΔΗΣ) G.; CHRISTOFI (Α. ΧΡΙΣΤ0ΦΗ) A.; ROSSIOS (Κ. ΡΩΣΣΙΟΣ) K. (Journal of the Hellenic Veterinary Medical Society, 2017)
In this paper it was examined the current status of sheep production in the area of Eordea of the prefecture of Kozani, that is mainly based in the semi-intensive system. The aim of this research was the collection of information of the current status of the sheep production sector with emphasis on its current problems and future perspectives. For this purpose, a questionnaire based research was conducted, using an objective sample (17.8%) of the total sheep farms in the area of Eordea from 16 separate settlements. The collection of the data and their statistical analysis gave a plethora of conclusions: the farms operate in a traditional way and have not been systematically upgraded; there is lack of uptake of new technologies (automated milking, artificial rearing and buildings). The low milk yields achieved are mainly due to the low genetic status of the animals used and the deficiencies in their feeding (non satisfactory combination between grazing and supplementary feeding, non rational feeding in the farm). Also, farms have high production costs due to their relatively small size and fractionation i.e. ineffective management. Other constraining factors include the age of farmers (they are old enough) and the unsatisfactory trade of the sheep products mainly due to the total lack of farmer cooperatives to market sheep products (milk, meat) and buy animal feeds. Although the sector of sheep husbandry does not seem to face at present intense antagonisms among the European Union countries, there are a lot of problems and disorders. However, many of the above mentioned problems may be overcome in the next years, through collaboration of sheep farmers with the relevant expert scientists, but also with the concern of the responsible services of the state.